Low impact of knowledge on compliance with COVID-19 precautions: Healthcare workers in Eswatini - Nompumelelo S. Ndwandwe; Charlotte Mokoatle; Shalin Bidassey-Manilal; Renay H. Van Wyk (Journal of Public Health in Africa)
Background: The increasing number of coronavirus disease 2019 (COVID-19)-related deaths among healthcare workers in Eswatini suggests that there may be suboptimal compliance with standard precautions among healthcare workers in the country.